Keeping it Safe: Extension Cords - Mary N. Harrison (EDIS)
Use extension cords only when necessary. It is best to plug an electrical device directly into the wall outlet if you can. That is not always possible. Outlets often are not in the locations where they are needed. To resolve this problem you will need an extension cord—you will also need the correct type of cord. Using the wrong kind of cord, or using it incorrectly can create safety hazards such as fire, shock, electrocution, trips and falls, and blown fuses. This document is FCS5233-03, one of a series of the Department of Family, Youth and Community Sciences, UF/IFAS Extension. Original publication date: May 2002. Revised: December 2005.